Mortality during pregnancy, childbirth and the puerperium. Cuba, 2005-2018 - Lisbeth Fernández González; Armando Humberto Seuc Jo; José Luis Peñalvo; Delia María Gálvez Medina; Armando Rodríguez Salvá; Alain Morejón Giraldoni (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: Maternal mortality in the world is unacceptably high. Complications in pregnancy, childbirth and the puerperium are the leading cause of death in women of childbearing age. In recent years the number of maternal deaths in Cuba, is one of the lowest in Latin America, but it is still far from the results of more developed countries. The most evident achievements are made in reducing infant mortality. Objective: to describe the behavior of deaths that occurs during pregnancy, childbirth and the puerperium in Cuba, in the period 2005-2018. Methods: an annual cross-sections descriptive study was carried out. The universe was the total deaths registered during pregnancy, childbirth and the puerperium in the period 2005-2018, in Cuba (N = 829). The mortality ratio, percentages, the trend and the average were calculated. Results: the death ratio during pregnancy, childbirth and the puerperium averaged 48.6 per 100,000 live births, as well as the average maternal mortality was 41.6. Direct obstetric deaths contributed 463, indirect 247; and for other deaths, there were 119. Conclusion: in the studied period, the behavior between the number of deaths and the ratio has been very similar, which indicates that the last one was determined mainly by the number of deaths and not by the number of live births. Direct obstetric deaths predominated, followed by indirect deaths, and then by the others. Indirect obstetric deaths were the only ones that showed a tendency to increase over time.